WATER RESOURCES AND HUMAN BEHAVIOUR: AN INTEGRATED LANDSCAPE MANAGEMENT PERSPECTIVE - Oosterbeek, Luiz; Scheunemann, Inguelore; Santos, Luís (Cadernos do LEPAARQ (UFPEL), 2013)
Abstract: A two sides balance can be drawn from the last 20 years of active intents to change local, regional and global policies concerning water and global environment issues. On one hand, as a consequence of the “sustainable development” model, there is an increasing awareness of the issues in stake, and environment became a core part of any public policy. International conferences and the investment in scientific research in these areas are an expression of this. Yet, concerns are growing in face of the increasing stress imposed on freshwater resources, climate change and the difficulties to achieve international consensus on specific strategies. This was the focus of discussion in the international conference on climate change organised in Nagoya in December 2010, by ICSS, ICSU and ICPHS. A revision of the conceptual approach to sustainable development, moving beyond a strictly socio-economic understanding of human behaviour and incorporating, as basic strategies, the dimensions of culture, didactics of dilemma and governance, is currently being applied in some scenarios, hopefully with a better result. The paper discusses water resources in the context of climate change from this integrated perspective.